Arte indígena contemporáneo. ¿Arte popular? - Sánchez Montañes, Emma (Revista Española de Antropología Americana, 2003)
Some proposes about the adjectives of the contemporary art made by the Native Americans, and the reality of the popular art are discussed. Different words and ideas are used in North America and Hispano America relative to native art are discussed